Law Enforcement Against Hazardous Waste Pollution Links to Environmental Protection (PT. Kimu Case Study) - Rismawati; Yuniar Rahmatiar; Muhamad Abas (Journal Equity of Law and Governance, 2024)
The purpose of this study is to determine the law enforcement against environmental pollution due to hazardous and toxic waste by PT Kimu Sukses Abadi. Regulations that regulate the problem of surrounding defilement made from industry enterprises that make hazardous and toxic mill cesspits require laws that can keep effect negative on their around neighborhood, videlicet reasonable laws. The inquiry of this learn is how to enforce criminal juristic opposed to conservationist pollution due to risk plus virulent waste and how is the element that hinders the effectiveness of Institute Numeric 32 of 2009 regarding ecological safeguard with administration. The near process utilized via the writer of researchers observational juridical, which is a study that emphasizes main statutory resources, namely interviews plus observations. The findings from this examination explain the weakness belonging to lawful Implementation inside handling alongside surrounding contamination due to hazardous and toxic materials carried out by companies due to negligence and weak supervision of law enforcement officials or related agencies that cause pollution of the surrounding environment so that river water becomes polluted and watersheds become damaged and very detrimental to the community and the Role of Local Governments in Law Enforcement Against B3 Waste Dirtiness is linked to Law Number 32 of 2009 pertains to the safeguarding and administration of environmental resources, namely 1) Supervision also Monitoring, 2) Implementation via administrative sanctions by the Regional Government, 3) The importance of coordination between the Regional Government and central agencies.